Public Hammams In Algeria During The Ottoman Period (Journal of Namibian Studies : History Politics Culture, 2024)
The current study includes three main chapters. The first one tackles an inventory of baths in the most important Algerian cities during Ottoman period refering to historical sources and modern studies, either the destroyed ones or those which are still exist nowadays. Besides, the second chapter treats the archaeological study by providing an archaeological description of some samples refering to the historical background and geographical location of each bath. Moreover, the third chapter is devoted to the analytical study of plans and architectural elements of baths which have been studied as a sample and others, through presenting the various planning styles, features and architectural characteristics of Algerian baths during the Ottoman period.